1990
DOI: 10.1116/1.576446
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh vacuum precise positioning device utilizing rapid deformations of piezoelectric elements

Abstract: Recently precise positioning devices with low outgassing rates have been required for production systems of very large scale integrated circuits, surface analysis systems, and scanning tunneling microscopes in ultrahigh vacuum. A bakable XYθ three-axis positioning table using a unique positioning mechanism utilizing friction and inertial forces caused by rapid deformations of piezoelectric elements was developed. The table has a hexagonal shape of 120 mm in diameter and is mainly made of aluminum alloys with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Most inertia motors described in the literature-especially those designed for microscopy applications-use hard materials for the friction couple. Aluminum oxide (Al 2 O 3 , sometimes as a ceramic, in most cases in crystalline form as corundum and its varieties sapphire and ruby) predominates [104,105,126,[153][154][155][156][157], but quartz (SiO 2 ) [49,104,154], different glasses [105,158,159], or other ceramics [158] are also used. Combinations of one of these hard materials and metals are also common, mostly with steel [30,44,51,52,78,96,139,160,161] or bronze [49,162,163], sometimes also with other metals [49,[164][165][166].…”
Section: Friction Couplementioning
confidence: 99%
See 1 more Smart Citation
“…Most inertia motors described in the literature-especially those designed for microscopy applications-use hard materials for the friction couple. Aluminum oxide (Al 2 O 3 , sometimes as a ceramic, in most cases in crystalline form as corundum and its varieties sapphire and ruby) predominates [104,105,126,[153][154][155][156][157], but quartz (SiO 2 ) [49,104,154], different glasses [105,158,159], or other ceramics [158] are also used. Combinations of one of these hard materials and metals are also common, mostly with steel [30,44,51,52,78,96,139,160,161] or bronze [49,162,163], sometimes also with other metals [49,[164][165][166].…”
Section: Friction Couplementioning
confidence: 99%
“…Higuchi, Yamagata et al [110,158] have shown that a parabolic rise of the voltage can be reasonable to reach a constant acceleration, and thus a constant inertial force. They also explain that the large acceleration occurring when the voltage stops increasing can be used to generate additional displacement in moving actuator motors (cp.…”
Section: Voltage Signals For Low-frequency Operationmentioning
confidence: 99%
“…Because the piezoelectric element is embedded into the moving element, this motor could be considered as a moving actuator type. Many of the inertia-drive type motors developed afterwards operate according to the above-mentioned initial structures [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. We can also find literature that proposes ideal driving signals with detailed analysis of motion at the interface [46,47].…”
Section: Inertia-drivementioning
confidence: 99%
“…Piezoelectric inertia drive motors have been used for both optical and scanning probe microscopes successfully in vacuum environments [65,66].…”
Section: Piezo-walk-drive-type Piezoelectric Motorsmentioning
confidence: 99%